Health-Related Quality of Life, Expectations and Academic Satisfaction of Young College Students - Jesus Alberto García-García; Daniella Carrizales-Berlanga (Interacciones)
Background: The study aimed to determine the relationship between the dimensions of health-related quality of life and the academic expectations of the outcome, future expectations, progress goals, and school satisfaction of young university students. Method: The research was observational, descriptive, correlational, and with a transitional design. In this study, 346 young university students (51% = men and 49% women) participated, from 18 to 23 years old, the form of a selection of the sample was for convenience. The SF-12 questionnaire was used, which evaluates the health-related quality of life in eight dimensions; physical function, physical role, body pain, general health, vitality, social function, emotional role, and mental health, and the scales of academic expectations of the outcome, academic progress goals, school satisfaction, and future expectations. Results: The results indicate the existence of high scores in physical function, physical role, and emotional role, except in social function. A correlation was observed between the physical health component and academic expectations, academic satisfaction, and future expectations. In turn, mental health is correlated with academic progress goals, academic expectations of the outcome, academic satisfaction, and expectations for the future. Conclusions: Young university students have a good quality of life, however, there is a proportion of students who do not adopt healthy habits and others do. Physical and mental health are important aspects in students; however, university students do not visualize the impact of these benefits on school success, the achievement of their academic expectations, progress goals, and even their future expectations.